Endosome-to-TGN Trafficking: Organelle-Vesicle and Organelle-Organelle Interactions - Tu, Yingfeng; Zhao, Lin; Billadeau, Daniel D.; Jia, Da (Frontiers in Cell and Developmental Biology, 2020)
Retrograde transport from endosomes to the trans-Golgi network (TGN) diverts proteins and lipids away from lysosomal degradation. It is essential for maintaining cellular homeostasis and signaling. In recent years, significant advancements have been made in understanding this classical pathway, revealing new insights into multiple steps of vesicular trafficking as well as critical roles of ER-endosome contacts for endosomal trafficking. In this review, we summarize up-to-date knowledge about this trafficking pathway, in particular, mechanisms of cargo recognition at endosomes and vesicle tethering at the TGN, and contributions of ER-endosome contacts.